Peningkatan Kompetensi Pedagogik dan Profesional Guru MGMP Bisnis Daring dan Pemasaran Provinsi Sumatera Barat Melalui Pelatihan Menggunakan Web-Blog - Rahmidani, Rose; Armiati, Armiati; Syukhri, Syukhri; Susanti, Dessi (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to improve the pedagogical and professional competence of MGMP teachers in the Online Business and Marketing Department of West Sumatra in terms of: a) designing a website and b) creating a blog. Training activities take place on Wednesday and Thursday, September 30, 2020 and October 1, 2020 at the UNP Faculty of Economics computer Labor. There were 20 participants who took part in this training, namely teachers of MGMP Online Business and Marketing, West Sumatra Province. The methods and approaches used are as follows: 1) Lecture and question and answer methods. 2) Training methods and individual guidance. 3) The method of recitation or assignment. The results of this service activity are: 1) Increased teacher competence in designing websites. The size of this increase can be seen from 85% of West Sumatra's MGMP teachers of the Department of Online Business and Marketing being able to produce websites. 2) Increased teacher competence in creating blogs. The size of this increase can be seen from the 85% of the MGMP teachers of the Online Business and Marketing Department of West Sumatra being able to create a blog.